2019
DOI: 10.7150/ijms.35037
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma S100A1 level is a risk factor for ST-segment elevation myocardial infarction and associated with post-infarction cardiac function

Abstract: Aim: To investigate the association between plasma S100A1 level and ST-segment elevation myocardial infarction (STEMI) and potential significance of S100A1 in post-infarction cardiac function. Methods: We examined the plasma S100A1 level in 207 STEMI patients (STEMI group) and 217 clinically healthy subjects for routine physical examination without a history of coronary artery disease (Control group). Baseline characteristics and concentrations of relevant biomarkers were compared. The relationship between S10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…S100A1 seems to be an essential factor concerning cardiological diseases since it is involved in the contractile performance of cardiomyocytes [36,37]. Fan et al demonstrated that patients showing ST-segment elevation myocardial infarction (STEMI) in the electrocardiogram (ECG) also had increased levels of S100A1 and that this S100 family member could complement current biomarkers [67]. It was also shown that S100A1 concentrations rise during early-stage acute myocardial ischemia, followed by a quick decrease, and thereby S100A1 could represent an early biomarker [68].…”
Section: Clinical Relevance Of S100 Proteinsmentioning
confidence: 99%
“…S100A1 seems to be an essential factor concerning cardiological diseases since it is involved in the contractile performance of cardiomyocytes [36,37]. Fan et al demonstrated that patients showing ST-segment elevation myocardial infarction (STEMI) in the electrocardiogram (ECG) also had increased levels of S100A1 and that this S100 family member could complement current biomarkers [67]. It was also shown that S100A1 concentrations rise during early-stage acute myocardial ischemia, followed by a quick decrease, and thereby S100A1 could represent an early biomarker [68].…”
Section: Clinical Relevance Of S100 Proteinsmentioning
confidence: 99%
“…Among the S100 family, S100A1 has the highest concentration in the myocardium, and its protein concentration level determines the likelihood of heart failure and contractile function following myocardial infarction (Rohde et al, 2014). Studies have shown that an elevated plasma S100A1 level is a significant predictor of STsegment elevation myocardial infarction, while there is reduced S100A1 expression in failing and hypertrophic heart tissues (Fan et al, 2019). The restoration of S100A1 expression to normal levels in failing cardiomyocytes using gene therapy can improve myocardial contractile function (Bennett et al, 2014;Brinks et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…S100A1, a predominant member of the S100 protein family, is a crucial regulator of cardiac contractility. Due to its ability to enhance sarcoplasmic reticulum Ca 2+ fluxes and increase SERCA2a enzyme activity, it can lead to the significant limitation of myocardial necrosis and development of HF [120]. A recent study conducted by Jungi and colleagues reported that S100A1 gene overexpression through the AAV9 vector can have cardioprotective effects in male Lewis rats after IRI.…”
Section: Gene Therapy To Reduce Apoptosismentioning
confidence: 99%